Regulatory Mechanisms of Presenilin on Kainate Receptor Currents at CA3 Pyramidal Cells in Alzheimer's Disease - Castanheira, Jorge Miguel Santos (2018)
Dissertação de Mestrado em Biologia Celular e Molecular apresentada à Faculdade de Ciências e Tecnologia